Correlation of computed tomography, magnetic resonance imaging and clinical outcome in acute carbon monoxide poisoning - Ozcan,Namik (2016)
Abstract Background and objectives: Carbon monoxide is a toxic gas for humans and is still a silent killer in both developed and developing countries. The aim of this case series was to evaluate early radiological images as a predictor of subsequent neuropsychological sequelae, following carbon monoxide poisoning. Case 1: After carbon monoxide exposure, early computed tomography scans and magnetic resonance imaging findings of a 52-year-old woman showed bilateral lesions in the globus pallidus. This patient was discharged and followed for 90 days. The patient recovered without any neurological sequela. Case 2: In a 58-year-old woman exposed to carbon monoxide, computed tomography showed lesions in bilateral globus pallidus and periventricular white matter. Early magnetic resonance imaging revealed changes similar to that like in early tomography images. The patient recovered and was discharged from hospital. On the 27th day of exposure, the patient developed disorientation and memory impairment. Late magnetic resonance imaging showed diffuse hyperintensity in the cerebral white matter. Conclusion: White matter lesions which progress to demyelination and end up in neuropsychological sequelae cannot always be diagnosed by early computed tomography and magnetic resonance imaging in carbon monoxide poisoning.